COMPARISON OF ONH, MACULA STRUCTURE AND HFA PATTERN IN HIGH MYOPIA AND EMETROPIA EYES WITH/WITHOUT GLAUCOMA - idhayu anggit widhasari; krisna dwi purnomo; Tatang Talka Gani; Retno Ekantini (Majalah Oftalmologi Indonesia, 2023)
Introduction: Axial length elongation contributes a challenge in myopia eyes due to morphological and visual field abnormalities. OCT instruments do not embed a normative database from high myopia. The study is aimed to compare Cirrus OCT and HFA parameters on high myopia and emetropia with/without glaucoma. Methods: This cross-sectional, prospective study was conducted at Sardjito General Hospital from 1st April 2021 to 11th May 2021. Patients with high myopia was enrolled with Spherical Equivalent (SE) ? -6D, 20 – 55 years of age. All participants underwent a complete ophthalmologic examination. Inclusion criteria: BCVA 20/40 or better, reliable visual field results. Result: From 22 eyes, there were no significant difference of age between high myopia with glaucoma/HMG (n=5), high myopia/HM (n=6), emetropia with glaucoma/EG (n=5), emetropia/E (n=6) with mean age was 36±3.2 y.o and 60% were male with SE -8.5±1.03D. Among ONH parameters, there were no differences between groups. In HMG, HM, EG, E group, median avgRNFL was 85um, 96.5um, 105um, 110um respectively. Thus, median vertical CD is 0.48, 0.40, 0.58, 0.55 in HMG, HM, EG, E group respectively. Whilst median GCIPL and visual index were 75um, 78.5um, 85um, 89.5um in HMG, HM, EG, E group respectively and had significantly different 0.012 (p<0.05) between groups. Median visual field index was 92%, 97%, 98% in HMG, HM, EG group respectively with significantly different 0.04 (p<0.05). Conclusion: The GCIPL and visual field index are significantly different between high myopia and emetropia with/without glaucoma